2008
DOI: 10.1002/elps.200700327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of band broadening in chemiluminescence detection coupled to pressurized capillary electrochromatography with an off‐column coaxial flow interface

Abstract: A system of off-column coaxial flow chemiluminescence (CL) detection coupled to pressurized CEC (pCEC) was described. The interface utilized a reactor that introduced postcolumn CL reagent into the capillary effluents in a sheathing flow profile. To compare and evaluate band broadening of analytes caused by the detector, the typical CL compounds luminol and N-(4-aminobutyl)-N-ethylisoluminol (ABEI) were separated and detected by pCEC or capillary HPLC (cHPLC) coupled to CL and UV detector, respectively. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Lin et al . demonstrated that the band broadening caused by the off‐column detection interface was minimized due to the fast kinetic nature of the CL reaction 33 using an off‐column coaxial flow interface in a CL detector coupled to pressurized CEC.…”
Section: New Ce Methodsmentioning
confidence: 99%
“…Lin et al . demonstrated that the band broadening caused by the off‐column detection interface was minimized due to the fast kinetic nature of the CL reaction 33 using an off‐column coaxial flow interface in a CL detector coupled to pressurized CEC.…”
Section: New Ce Methodsmentioning
confidence: 99%
“…Due to the simplicity and versatility, UV detection is widely used for determination of phytochemical bioactive components by CEC (Tables 1 and 2), but MS is rarely used 41. Actually, several detection methods, including coordination ion spray MS 129, thermo‐optical absorbance detection 130, ion trap storage reflectron TOF MS 131, 132, condensation nucleation light scattering detection 133, NMR 134–136, LIF 84, 137–142, amperometric detection 143–146, indirect spectrophotometric detection 147, chemiluminescence detection 148–151 and matrix‐assisted laser desorption/ionization MS 152, have been successfully applied for the detection of CEC. Therefore, different detection coupled with CEC for analysis of phytochemical bioactive compounds should be employed to improve the sensitivity and specificity, especially for the bioactive compounds without UV absorptivity.…”
Section: Application Of Cec In Phytochemical Analysismentioning
confidence: 99%
“…In the past few decades, the applicability of CL detector connected with CE or microchip CE has been clearly demonstrated [16 -28], and been successfully applied to the determination of metal ions, clinical medicine, carbohydrates, and peptides and so on. In recent 2 years, our group has made extensive efforts to develop the diverse pCEC-CL detection modes that include on-column coaxial flow [29], offcolumn coaxial flow [30] as well as end-column reservoir [31]. The feasibilities of pCEC-CL systems have been fully validated by the evaluation and comparison of its detection mode in technology and methodology.…”
Section: Introductionmentioning
confidence: 99%